Application of flipped classroom technique in teaching bachelor students majoring in law - Dmitriy I. Kislitsyn, Nadezhda T. Sukhanova; Nikolay I. Lapin, Viktor A. Tarasov, Svetlana A. Balunova, Sergei V. Boldin (Opción, 2020)
The article shares the experience of using the „Flipped Classroom‟ model in a pedagogical university and examines the results of using this technique when teaching Multimedia Technologies. Theoretical, empirical, experimental methods and methods of quantitative and qualitative assessment of the results were used. As a result, blended learning is an effective method of improving the quality of students‟ training. In conclusion, it is such an organization of the learning process which supports the development of qualities and skills: cooperation, creativity, ability to solve problems, self-reliance, and ICT literacy. This provides an opportunity to support their development in each student.